Dar al retrato nueva luz. Vicente Carducho, Lázaro Díaz del Valle y el género del retrato en España en el siglo xvii - José Riello (Mélanges de la Casa de Velázquez, 2025)
Over the last two decades, several leading publications and a series of temporary exhibitions have revealed the semantic and formal complexity that characterised portraiture in the modern period. In Spain, and during the seventeenth century, there was a close link between pictorial theory and practice concerning genre; in a way, this circumstance sets it apart from other pictorial genres, and especially from religious painting, which, from my point of view, departs from what contemporary image theory proposes. This article will review the claim about the portrait made by the authors of the main Spanish treatises and, in particular, by Lázaro Díaz del Valle: cantor of the Royal Chapel with a passion for genealogy, and also for pictorial art; he was also known to several of the best Spanish painters of his time, including Diego Velázquez. His manuscript on painting, written between 1656 and, at least, 1662, is linked to the painter’s artistic and noble aspirations, and could in fact be considered a sui generis treatise on portraiture.